ANATOMI TUJUH JENIS KAYU DARI SULAWESI TENGAH. (Anatomy of seven Wood Species from Central Sulawesi) - Y I Mandang (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Wood anatomy of three broad-leaved tree species and four coniferous tree species from Central Sulawesi were observed and described for identification purposes. Fiber dimensions were also measured for evaluation of their quality for pulp making.The three broad-leaved woodspecies (Pouteria firma, Castanopsis javanica and Tristania maingayi) are different in many aspects of wood anatomy so that they are easy to identify. The four coniferous wood species (Agathis philippinensis, Podocarpus imbricatus, Phylocladus hypophylus and Dacrydium beccarii) are similar in many aspects of wood anatomy so that they are difficult to distinguish from each other. More material is needed for furher observation.No single species among the three broad-leaved wood species contain fibers with good quality. All of the four coniferous wood species contain fibers which are moderately good for pulp.